Acrochordon With Histological Features of Lichen Sclerosus. (June 2019) - Arnold, Kathryn A.; Sundharkrishnan, Lohini; Bolotin, Diana; Shea, Christopher R.
Abstract : Abstract: Lichen sclerosus (LS) is a chronic inflammatory dermatosis that classically presents as sclerotic, atrophic plaques in the genital region. We present a case of acrochordon with histological features of LS, clinically mimicking intradermal nevus, in a 53-year-old man with no prior history of LS. Our case highlights an unusual morphologic variant of acrochordon and illustrates the role of chronic pressure and occlusion in the development of secondary features of LS.